Social representations of psychologists on drugs consumptions, consumers and treatments - Gaete, Tomás (Revista de Psicología, 2007)
The present research is intended as a contribution to the knowledge and understanding of drug dependence through a descriptive analysis of the social representations that psychologist have that are inserted in programs of prevention, treatment and rehabilitation of drug consumption. It involves, as well, the representations that are developed of the addicted subjects undergoing drug treatment. The problem lies in the fact that drug addiction not only has become a question of mental health, but of citizen security, which gives the drug addict a double connotation: that of patient and delinquent. This cultural arbitrary concept of the addict lies within tjhe terapeutic context. For this reason it is possible that the practice of prevention, treatment and rehabilitation exerted by psychologists, respond to the social connotation of the addicted subject.